Campylobacter in Wild Birds: Is It an Animal and Public Health Concern? - Ahmed, Nejash A.; Gulhan, Timur (Frontiers in Microbiology, 2022)
Campylobacteriosis continues to be the leading cause of foodborne bacterial zoonotic infections worldwide. Despite its public health importance, the status of this disease in wild birds and the possibility of transmission from wild birds to domestic animals and humans have not been clearly elucidated yet. This article reviews the available literature with the aim of making a comprehensive manuscript on this disease status in wild birds and the possibility of interspecies transmission. Campylobacter has been isolated from various species of wild birds worldwide, with C. jejuni being the most commonly isolated species. The prevalence of Campylobacter in wild birds may vary depending on several factors like geographical location, seasonality, the bird's health status, bird species, sample type, the method used, and ecological factors. Molecular studies over the past two to three decades have characterized Campylobacter strains isolated from wild birds and have come up with results that fall into two categories. The first are those that report overlapping strains among human, domestic animal, and wild bird isolates. The results of the studies under this category emphasize that wild birds carry strains of Campylobacter, which are indistinguishable from domestic animals and humans and are therefore an important public and animal health concern. In contrast, the studies under the second category highlight significant differences in Campylobacter population structure among these hosts. Despite the controversiality and the inadequacy of current research to draw a full concussion, the role of wild birds in the epidemiology of Campylobacter should not be undermined as drug resistant-strains, especially resistance to tetracyclines and fluoroquinolones, are increasingly documented. In addition, source attribution studies have linked human cases of Campylobacter infections to wild birds. Therefore, the role of wild birds in the epidemiology of Campylobacter infection should not be neglected. However, in order to determine disease status in wild birds and the precise role of wild birds in domestic animals and human health, detail-oriented epidemiological investigations characterizing the genetic relatedness of isolates from the respective species and environment through one health approach are warranted.